Hegemoni Khulafa’ Al-Rasyidin Dalam Penerapan Kebijakan Taqlil Al-Riwayah - Azhar, Fahmi; Abdullah Musfi, Abdulbasith Abduljalil (Indonesia, 2023)
This article examines Khulafa’ al-Rasyidin's policy of imposing restrictions on the transmission of hadith which began to develop at that time. The implementation of the taqlil al-riwayah policy is quite different and seems to conflict with the time of the prophet. During the time of the Prophet, the companions were asked to spread the words of the Prophet to people who did not know them, but during the time of the Khulafa’ al-Rasyidin they adopted a policy of limiting (al-tathabut fi riwayah) and reducing transmission (taqlil al -riwayah). So ultimately the policies taken are contrary to what the prophet ordered. In this research, the method used is qualitative-descriptive through library research. The results of this study show that the implementation of the taqlil al-riwayah khulafa' al-rasyidin policy had a major influence on the development of hadith after the Prophet's death. As a religious leader, the caliph of course takes care of matters relating to religious affairs as well as the hadiths of the prophet. The taqlil al-riwayah policy is a form of caution in transmitting hadith from irresponsible people. The caliphs' caution in narrating hadith from the prophet was simply fear and worry of making mistakes in the hadith either being tainted by lies or alterations.